Triple Role Pada Perempuan Orang Asli Papua Dalam Rumah Produksi D’TOMU : Studi Implementasi Perda Nomor 1 Tahun 2019 Tentang Pengakuan dan Perlindungan Masyarakat Hukum Adat di Kampung Sebyar Rejosari, Distrik Tomu, Kabupaten Teluk Bintuni, Provinsi Papua Barat - Sinta Juliyanti (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
Empowering women through the development of home-based industries plays a crucial role in improving household welfare and strengthening community-based economies in Papua. This study aims to analyze the triple role of Indigenous Papuan Women (OAP) in the D’TOMU Home Production in Sebyar Rejosari Village, Tomu District, Teluk Bintuni Regency, and to evaluate the implementation of Regional Regulation No. 1 of 2019 concerning the Recognition and Protection of Indigenous Peoples’ Rights. This research employs a qualitative method using in-depth interviews, observations, and documentation with ten key informants, including OAP women, community leaders, and production facilitators. The findings indicate that the home production initiative has a significant positive impact on three main aspects: (1) better time management balance in handling domestic, productive, and social roles; (2) increased household income by 25%–35% through product diversification such as sago flour, keladi chips, fish crackers, shrimp crackers, and traditional Papuan handicrafts; and (3) improved social recognition of women within families, communities, and indigenous societies. This study highlights the importance of government support, entrepreneurship training, digital literacy enhancement, and multi-stakeholder collaboration to achieve sustainable and competitive empowerment of Indigenous Papuan women.